Attenuation of Mycoplasma hyopneumoniae Strain ES-2 and Comparative Genomic Analysis of ES-2 and Its Attenuated Form ES-2L - Li, Zhenya; Wang, Yingxin; Zhang, Yanyan; Tang, Xibiao; Wang, Xiangru; Liu, Wenhao; Qian, Yulin; Zhu, Yongwei; Chen, Huanchun; Tan, Chen (Frontiers in Veterinary Science, 2021)
Mycoplasma hyopneumoniae causes swine respiratory disease worldwide. Due to the difficulty of isolating and cultivating Mycoplasma hyopneumoniae, very few attenuated strains have been successfully isolated, which hampers the development of attenuated vaccines. In order to produce an attenuated M. hyopneumoniae strain, we used the highly virulent M. hyopneumoniae strain ES-2 which was serially passaged in vitro 200 times to produce the attenuated strain ES-2L, and its virulence was evidenced to be low in an animal experiment. In order to elucidate the mechanisms underlying virulence attenuation, we performed whole-genome sequencing of both strains and conducted comparative genomic analyses of strain ES-2 and its attenuated form ES-2L. Strain ES-2L showed three large fragment deletion regions including a total of 18 deleted genes, compared to strain ES-2. Analysis of single nucleotide polymorphisms (SNP) and indels indicated that 22 dels were located in 19 predicted coding sequences. In addition to these indels, 348 single nucleotide variations (SNVs) were identified between strain ES-2L and ES-2. These SNVs mapped to 99 genes where they appeared to induce amino acid substitutions and translation stops. The deleted genes and SNVs may be associated with decreased virulence of strain ES-2L. Our work provides a foundation for further examining virulence factors of M. hyopneumoniae and for the development of attenuated vaccines.